Daily field checking list by Walter Rosene, April 14, 1940 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Dunbar Slough and the Des Moines River by Walter Rosene, Robert Walker, Samuel J. Hyde and Earl Peterson, April 14, 1940. Also notes he observed a flock of Plovers and many ducks and geese. Plustek--flatbed